Zapadnjački pogledi na književnost - Hergešić, Ivo ([S. l.] : [s. n.], 1935)
O pogledima Fernanda Baldenspergera ; faks. rukopisa F. Baldenspergera.
P. o.: ["Hrvatska revija". ; god. 8/1935.].
Bibliografija: str. 15.